2004
DOI: 10.3354/meps277079
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous role of phlorotannins as chemical defenses in the brown alga Fucus vesiculosus

Abstract: Brown seaweeds (Fucales) produce phlorotannins that are often considered chemical defenses against herbivores. The many correlative and fewer direct tests conducted have shown effects of phlorotannins on herbivore feeding behavior to be variable. In an attempt to clarify the roles of phlorotannins versus other metabolites in defending brown algae, we conducted bioassay-guided fractionation of herbivore-deterrent extracts from the commonly studied brown alga Fucus vesiculosus. Feeding by the amphipods Ampithoe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 62 publications
(112 reference statements)
4
41
1
Order By: Relevance
“…Algal palatability after induction of phlorotannins stimulated (Pavia et al 1997), decreased, or did not affect seaweed consumption by the mesograzers Littorina obtusata or Idotea granulosa. Also, even at elevated concentrations, phlorotannins lack repulsive effects against at least some mesograzers, including amphipod species (Kubanek et al 2004). The rigorous bioassay guided study of Deal et al (2003) revealed that F. vesiculosus compounds, which were repulsive to urchins, were neither within the phlorotannin-nor the DCM-soluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Algal palatability after induction of phlorotannins stimulated (Pavia et al 1997), decreased, or did not affect seaweed consumption by the mesograzers Littorina obtusata or Idotea granulosa. Also, even at elevated concentrations, phlorotannins lack repulsive effects against at least some mesograzers, including amphipod species (Kubanek et al 2004). The rigorous bioassay guided study of Deal et al (2003) revealed that F. vesiculosus compounds, which were repulsive to urchins, were neither within the phlorotannin-nor the DCM-soluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, phlorotannin standards were made by grinding (Power Gen 500 homogenizer; Fisher Scientific, Hampton, NH, USA) and extracting frozen kelp tissee Arnold 1998, Amsler andFairhead 2006). The function and effectiveness of phlorotannins as feeding deterrents may differ by algal and herbivore species, with some studies demonstrating grazing reduction or inhibition (Geiselman andMcConnell 1981, Pavia andToth 2000a) and others showing negligible responses or even increased herbivory (Steinberg and van Altena 1992, Deal et al 2003, Kubanek et al 2004.…”
Section: Phlorotannin Analysismentioning
confidence: 99%
“…Briefly, phlorotannin standards were made by grinding (Power Gen 500 homogenizer; Fisher Scientific, Hampton, NH, USA) and extracting frozen kelp tissee Arnold 1998, Amsler andFairhead 2006). The function and effectiveness of phlorotannins as feeding deterrents may differ by algal and herbivore species, with some studies demonstrating grazing reduction or inhibition (Geiselman and McConnell 1981, Pavia andToth 2000a) and others showing negligible responses or even increased herbivory (Steinberg and van Altena 1992, Deal et al 2003, Kubanek et al 2004.Phlorotannin content in brown algae can be regulated by a variety of abiotic and biotic variables, with large species-specific variability in responses to these factors (reviewed by Amsler and Fairhead 2006), which may act synergistically to affect distribution of phlorotannins within species and within thalli (e.g., Hay 1996, Targett and Arnold 1998). Phlorotannin content may be influenced by temporal variability in physical factors such as irradiance Toth 2000b, Cruces et al 2012), salinity (reviewed by Ragan and Glombitza 1986), nutrients (Yates and Peckol 1993, Cronin and Hay 1996, Svensson et al 2007, and water movement (Dayton 1985).…”
mentioning
confidence: 99%
“…These responses are likely to have a major impact on the population biology and life history of the inducing consumer because they suppress both herbivore feeding and egg hatching rates (Toth et al 2005). The underlying mechanism of induction observed in these studies may involve chemical defenses of A. nodosum because (1) artificial foods made from induced seaweeds lacking morphological defenses also suppressed snail grazing and (2) snail grazing increased the concentration of phlorotannins , Toth et al 2005, which are widely thought to serve as defensive compounds in brown algae (but see Kubanek et al 2004 for an exception). Recent evidence suggests that a southern England A. nodosum population also exhibits inducible defenses that suppress herbivore feeding and alter habitat preference (Borell et al 2004).…”
Section: Introductionmentioning
confidence: 99%